2018
DOI: 10.3390/jcm7080183
|View full text |Cite
|
Sign up to set email alerts
|

Calcification Patterns in Papillary Thyroid Carcinoma are Associated with Changes in Thyroid Hormones and Coronary Artery Calcification

Abstract: Recent studies suggested that a lower serum thyroid hormone level is associated with more vascular calcification. However, it has been rarely evaluated whether lower thyroid hormone levels affect the calcification of thyroid cancer and there is a relationship between calcification patterns of papillary thyroid carcinoma (PTC) and coronary artery calcification (CAC). The study was divided into two groups: First, we retrospectively reviewed 182 PTC patients and examined the correlation between PTC calcification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In our study, the prevalence of microcalcification in the PTC group was 64.2% (77/120) and 37.0% (61/165) in the PTMC group; these frequencies were greater than those reported by Ha et al (30.5%, 108/354) and Oh et al (35.9%, 136/379). 43 , 44 The difference could be attributed to our classification of microcalcification; we included other types of calcification with microcalcification. Besides, microcalcification in the PTMC group with CLNM was greater than without CLNM (55.6% vs 30.0%, P =0.002).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of microcalcification in the PTC group was 64.2% (77/120) and 37.0% (61/165) in the PTMC group; these frequencies were greater than those reported by Ha et al (30.5%, 108/354) and Oh et al (35.9%, 136/379). 43 , 44 The difference could be attributed to our classification of microcalcification; we included other types of calcification with microcalcification. Besides, microcalcification in the PTMC group with CLNM was greater than without CLNM (55.6% vs 30.0%, P =0.002).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of microcalcification is different from that of macrocalcification. The former is closely related to psammoma, while the latter is mainly interstitial calcification and ossification [33,34]. However, whether macrocalcification affected the efficacy of RFA is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastasis and extrathyroidal invasion are associated with aggressive features in PTC [ 16 , 29 31 ]. Of the concomitant PTC cases, 43.5% had lymph node metastasis and presented with extrathyroidal invasion, suggesting high-risk features [ 16 , 29 31 ]. A previous study reported that the optimal LNR threshold value for predicting PTC recurrence was 17.86% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microcarcinoma was defined as cancer where the greatest dimension was ≤1 cm. The calcification pattern was classified into the following three groups according to the consensus statement and recommendations proposed by the Korean Society of Thyroid Radiology and the Korean Society of Radiology [ 15 ]: (1) no calcification; (2) microcalcification defined as the presence of punctate echogenic foci of <1 mm with or without posterior shadowing; (3) macrocalcification defined as the presence of echogenic foci >1 mm with posterior shadowing [ 16 ]. The Korean Thyroid Imaging Reporting and Data System (K-TIRADS) was used to classify preoperative thyroid nodules for biopsy recommendation [ 17 ].…”
Section: Methodsmentioning
confidence: 99%